CAMPUS’ INFORMAL LEARNING SPACES FOR READING ACTIVITIES AND THEIR RELATION TO UNDERGRADUATES’ RESPONSES - Angela Christysonia Tampubolon; Hanson E Kusuma (DIMENSI (Journal of Architecture and Built Environment), 2019)
Potential of informal learning spaces (ILS) in promoting reading activities are one of a theme of space that can be explored in higher education. This explanatory study was aimed at identifying ILS at selected university which preferred by students as reading space and their relation to students’ responses. Students tend to choose library ILS but non-library ILS also have potential in supporting the responses to be achieved. Students were found to have better comprehension, a good mood, and to read longer in library ILS. Meanwhile, students found it easier to pay attention and felt an increased desire to engage in discussions in non-library ILS, and tended to visit these more often. At this case study, library ILS tends to be used for individual activities, while non-library ILS are used for collaborative or group activities. Adapting function and type of space between ILS categories can be part of efforts to create learning engagement and to support both individual and collaborative work.